Sequential Organization of Indonesian Stand-Up Comedy Performance - Dwi Indarti (LPPM Universitas Bina Sarana Informatika, 2020)
Stand-up comedy is a popular phenomenon entertainment featuring a solo performer, called as Comic who narrates a comical story in front of live audiences. Since it was first developed in the United States, stand-up comedy has been flourishing all over the world. Stand-up comedy programs have become the most interesting television shows in Indonesia. It could be seen by the number of programs in some local television channels. One of them is SUCI (Indonesian Stand-up Comedy) broadcasted by Kompas TV. SUCI is a stand-up comedy competition purposes to seek the best Indonesian Comic. This paper aims to analyze the sequential organization of three Indonesian Comics who performed in Grand Final SUCI season five. Using the serial sequential organization proposed by Scarpetta and Spagnolli (2009) as the theoretical framework, this study outlines the narrative of the stand-up comedy’s texts and seeks whether there is a difference between the three finalists of SUCI 5 in delivering their narratives.